Fatal disseminated cryptococcosis following intraocular involvement. Issue 3 (March 1988) - Schulman, J A; Leveque, C; Coats, M; Lawrence, L; Barber, J C
Abstract : A 33-year-old man was treated with systemic steroids for a retinal inflammatory lesion before the diagnosis of cryptococcal retinitis and meningitis was suspected. He died from central nervous system disease despite treatment with parenteral antifungals. Histopathological studies demonstrated ocular and disseminated systemic infection with Cryptococcus neoformans. Direct cryptococcal involvement of the eye is rare and is usually associated with disseminated disease. Systemic steroids must be used with caution, and patients who take these drugs require frequent monitoring.